2006
DOI: 10.1080/14767050600852510
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of third trimester uterine artery flow velocity indices in relationship to perinatal complications

Abstract: RI and PI as measures of third trimester utero-placental vascular impedance are the best predictors of adverse outcome of IUGR-suspected pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Becker and Vonk [3] found that deep notching in the uterine arteries at 20 -23 weeks was associated with adverse pregnancy outcome. In contrast, Ghosh et al [12] suggested that the uteroplacental vascular impedance was a better predictor than the presence of notching in the third trimester for adverse outcome of SGA suspected pregnancies. Furthermore, we did not record the rate of labor induction in our study population.…”
Section: Discussionmentioning
confidence: 88%
“…Becker and Vonk [3] found that deep notching in the uterine arteries at 20 -23 weeks was associated with adverse pregnancy outcome. In contrast, Ghosh et al [12] suggested that the uteroplacental vascular impedance was a better predictor than the presence of notching in the third trimester for adverse outcome of SGA suspected pregnancies. Furthermore, we did not record the rate of labor induction in our study population.…”
Section: Discussionmentioning
confidence: 88%
“…15 This is in contrast to the findings of Ghosh et al where RI and PI were considered better indicators of vascular impedance in predicting adverse perinatal outcomes. 16 B/L notch in uterine artery Doppler was present in 25.4% participants and this findings are quit comparable with the similar study done by Wald RM et al, Rai L et al but not consistent with study done by Maria AL et al and Li H et al 11,13,14,17 Study found acceptable sensitivity, specificity, PPV and NPV of Doppler ultrasound during third trimester to predict obstetrical and perinatal outcome and this findings are comparable with study done by Rai L et al 13 Limitations of this study was number of cases has been small and study not included Patients who came in labor or with a complication like abruptio placenta.…”
Section: Discussionmentioning
confidence: 99%
“…These babies are at increased risk of preterm birth (30,31). Moreover, there is controversy surrounding the risk of respiratory distress syndrome (RDS) in this obstetric subgroup (12), which may be in part attributable to the heterogeneous causes of IUGR (maternal, fetal, and/or placental factors; reviewed in Refs.…”
mentioning
confidence: 99%